IMPLEMENTASI HIDEN KURIKULUM DALAM MEMBENTUK KARAKTER RELIGIUS MAHASISWA MA’HAD AL-JAMI’AH UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN - Alwi Fadli Trimala; Zainal Efendi Hasibuan (Yayasan Baitul Hikmah al-Zain, 2025)
One of the strategies implemented to achieve learning objectives is through the implementation of a hidden curriculum. This type of research is descriptive qualitative about hidden curriculum which will describe the religious character of students at the Syekh Ali Hasan Ahmad Addary Padangsidimpuan State Islamic University, involving interviews, observation and document analysis to understand the impact on students' religious character. The implementation of this hidden curriculum increases learning, with the hidden curriculum it does not directly change students' mindsets but gradually changes their habits with the hidden curriculum. Although much research has been conducted on the implementation of the hidden curriculum, especially in the context of its religious character, there is still some lack of research and room for further research, the local context of Ma'had al-Jami'ah, the role of teaching and administrative staff and students' understanding of the hidden curriculum. .